Economics of crime a reader - Alper, Neil 1949-; Hellman, Daryl A. (Simon & Schuster Custom Publishing, 1997)
This book of readings is designed to accompany The Economics of Crime. The readings are arranged to follow the orgainization of thet text, and are selected to complement the material presented in the text. The readings represent both theoretical and empirical studies, examining issues central to the economic approach to either understanding criminal behaviour or to developing effective public policy for dealing with crime. While some papers are written by economists, others come from related disciplines.